2002
DOI: 10.1021/ie010571f
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production at Flask and Pilot Scale from Concentrated Slurries of Steam-Exploded Aspen

Abstract: This paper investigates the production of ethanol from steam pretreated aspen. The optimal conditions for both the pretreatment and ethanol production were determined. In the former step the parameters investigated were temperature (180-220 °C) and residence time (2-6 min). The most effective combination was 214 °C and 6 min. The exploded substrates were detoxified in three ways, washing with water at 65 °C proving to be the most effective. The substrate was then converted into ethanol via simultaneous sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…Mohagheghi et al (1992) used the dilute acid pretreated wheat straw at a solids loading of 32.3% (w/w) and achieved the maximum ethanol concentration of 57 g/L after 144 h SSF operation. De Bari et al (2002) used the steam exploded aspen wood at a solids loading of 16% (w/w) with hot water washing for detoxification and the optimal ethanol concentration of 47 g/L in the fermentation flask. Jørgensen et al (2007) used the steam pretreated wheat straw at a solids loading of 35% (w/w) and the ethanol concentration reached 62 g/L (converted from the value of 48 g/kg (w/w) in the original reference for easy comparison) after 96 h SSF operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohagheghi et al (1992) used the dilute acid pretreated wheat straw at a solids loading of 32.3% (w/w) and achieved the maximum ethanol concentration of 57 g/L after 144 h SSF operation. De Bari et al (2002) used the steam exploded aspen wood at a solids loading of 16% (w/w) with hot water washing for detoxification and the optimal ethanol concentration of 47 g/L in the fermentation flask. Jørgensen et al (2007) used the steam pretreated wheat straw at a solids loading of 35% (w/w) and the ethanol concentration reached 62 g/L (converted from the value of 48 g/kg (w/w) in the original reference for easy comparison) after 96 h SSF operation.…”
Section: Discussionmentioning
confidence: 99%
“…Mohagheghi et al (1992) reported a simple horizontally rotating fermenter for SSF at the maximum solids loading of 24.4% (w/w) dilute acid pretreated wheat straw after washed with deionized water. De Bari et al (2002) demonstrated an experimental flowsheet for ethanol production from aspen wood at the maximum solids loading of 16% (w/w). The steam exploded aspen wood was either soaked with alkali or washed with hot water for detoxification of degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…Only few plants are available worldwide to investigate the process (pretreatment and bioconversion) at demo scale. More recently, the steam explosion pretreatment, investigated for several years in Italy at the ENEA research Center of Trisaia (De Bari et al, 2002, 2007, is now going to be developed at industrial scale thanks to investments from the Italian Mossi & Ghisolfi Group.…”
Section: Pretreatmentmentioning
confidence: 99%
“…A steam temperature of 225°C and pretreatment time of 5 min were applied to realize a severity parameter value of log Ro = 4.37, which ensured a significant reduction of DP with the lowest degradation and produced a material more suitable for hydrolysis (De Bari et al, 2002). After the saturated steam exposure, a ball valve at the bottom of the reactor was opened suddenly to bring the reactor rapidly to atmospheric pressure.…”
Section: First Stage Pretreatmentmentioning
confidence: 99%